Orchidopexy in Late Childhood often Associated with Previously Normal Testicular Position - van der Plas, Evelyn; Zijp, Gerda; Froeling, Frank; de Wilde, Jeroen; van der Voort, Laszla; Hack, Wilfried (European Journal of Pediatric Surgery, 2013)
Introduction The aim of this study was to determine retrospectively, the prevalence of acquired undescended testis (UDT) in boys who underwent late orchidopexies, that is, performed after the age of 2 years.Methods We included all patients who were 2 years or older when they underwent orchidopexy (ORP) for UDT at the Juliana Children's Hospital during 1996 to 2009. Previous testis position from birth until the date of ORP was obtained from youth health care records.Results We identified 660 boys who underwent ORP after the age of 2 years for undescended testis. For 421 of these 660 boys, the previous testicular position could be retrieved from the health records. In 143 of these 421 boys (34%), the operated testis had never been scrotal (congenital UDT), whereas in the other 278 boys (66%), a previous scrotal position had been documented twice or more (acquired UDT).Conclusion Our results show that two-thirds of the boys that underwent ORP after the age of 2 had previously normal descended testes. This finding may offer an additional explanation for the discrepancy between the incidence of congenital UDT and the high rate of ORP in mid and late childhood.
Keywords: cryptorchidism; orchidopexy; pediatric